Indonesian Press History: Literature Study of Press History Research in Indonesia - Lukas Maserona Sarungu; Siswanta Siswanta; Yantika Nur Cahyati (ETTISAL : Journal of Communication, 2022)
The absence of a map on the history of Indonesian Press makes it difficult for communication researchers to understand the scope of this field. The purpose of this study is to provide an up-to-date description of the historical researches of newspapers in Indonesia. The literature study method is used to select, sort and map various research literature on the history of newspapers in Indonesia. The result of this study is a mapping diagram of newspaper history that divides press history research into 5 genres, namely: local press, media organizations, ideology and propaganda, media history in general, and press bans. The implication is that this diagram can be used as a basis for press history researchers to gain insight into the themes and timeframes that have been researched by the researchers and at the same time open up opportunities for which themes and timeframes still need further investigation. Ketiadaan peta mengenai riset sejarah surat kabar menyulitkan peneliti komunikasi untuk memahami ranah penelitian tersebut. Tujuan penelitian ini berusaha untuk memberikan gambaran terkini tentang penelitian-penelitian sejarah surat kabar di Indonesia. Metode studi literatur digunakan untuk memilih, memilah dan memetakan beragam literatur penelitian sejarah surat kabar di Indonesia. Hasil kajian ini adalah diagram pemetaan sejarah surat kabar yang membagi riset sejarah pers kedalam 5 genre, yaitu: pers lokal, organisasi media, ideologi dan propaganda, sejarah media secara umum, dan pembreidelan pers. [A1] [A2] Implikasinya, diagram ini dapat dijadikan dasar bagi para peneliti sejarah pers untuk mendapatkan wawasan mengenai tema dan timeframe yang telah diriset oleh para peneliti dan sekaligus membuka peluang bagi tema dan timeframe mana saja yang masih perlu untuk diteliti lebih lanjut.  [A1]Tambahkan tujuan, metode dan hasil scr eksplisit [A2]Done: saya tambahkan dan saya beri Bold. Terima kasih